El derecho de consumo: notas sobre su repercusión - Mondéjar, Ignacio Andrés (REVISTA PROCESOS DE MERCADO, 2014)
Law has helped humankind, before human beings were considered consumers or entrepreneurs, to obtain stability, peace and trust in their relations, especially in their business relations. This type of Law between civilians was, together with a corrective criminal law, the one that arose spontaneously in all civilizations. The regulations or traditions may be different but the nature of those spontaneous rules is equivalent. However, the State has been involved in a number of areas of the Right to parties, being the labour law, which regulates the rules between entrepreneurs and employees, and the consumer law, which regulates the rules between entrepreneurs and consumers, two of the most remarkable State’s interventions. Key words: Law, State, Consumption, Regulation, Arbitrage. JEL Classification: D11,D18, K10, K12, K13, P36. Resumen: El derecho ha servido a los hombres, antes de que se les denomi - nara consumidores y empresarios, en su afán de dar estabilidad, paz y fir-meza en sus relaciones, sobre todo y ante todo en sus relaciones comerciales. Este tipo de derecho entre civiles fue junto con el derecho penal correctivo, el que surgió espontáneamente en todas las civilizaciones. La regulación o las costumbres serán diferentes pero la esencia de esas espontáneas normas sí son equivalentes. Sin embargo, el Estado se ha introducido en numerosas parcelas del derecho de partes destacando aquí el derecho laboral, re gulan-do las normas entre empresarios y trabajadores y el derecho de consumo regulando las normas entre empresarios y consumidores. Palabras clave: Derecho, Estado,Consumo, Regulación, Arbitraje. Clasificación JEL: D11,D18, K10, K12, K13, P36.